Equality and Difference in Olympe de Gouges' Les droits de la femme. A La Reine. Issue 4 (2nd October 2019) - Reuter, Martina
ABSTRACT: This article examines Olympe de Gouges' demands for the rights of woman in her famous but still understudied work Les droits de la femme. A La Reine [1791]. Particular emphasis is put on analysing how she combines her demand for equality with her conception of sexual difference. The article consists of three parts. The first part gives a brief overview of the demands for the equality of the sexes as they were presented in seventeenth-century France and critically reacted upon in eighteenth-century France, not least by Jean-Jacques Rousseau in his defence of sexual difference. The second and third parts focus on Gouges' argumentation. First, by analysing how she argues for women's active citizenship by criticising the exclusion of women from the public sphere, but without questioning sexual difference as such; and second, by discussing how she redefines the famous slogan of the French Revolution; liberty, equality, fraternity. The conclusion argues that rather than being caught in a paradox of equality and difference, as has been claimed by Joan W. Scott, Gouges did successfully combine the two concepts, even if her interpretation of their relation was excluded from the canon of political theory.